Determination of Upper Reference Limit for High-Sensitivity Troponin T in Chronic Kidney Disease Patients - Naz, Sehrish; Muhammad Qaiser Alam Khan; Asma Hayat; Sikander Hayat Khan; Sajida Shaheen; Anser Umar Khan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To establish the 99th percentile of upper reference limit (URL) for high-sensitivity Troponin T (hs-Troponin T) in patients with Chronic Kidney Disease (CKD). Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Jan to Jun 2025. Methodology: A total of 300 males and 300 females were enrolled. Patients with CKD stages 3 to 5, based on estimated glomerular filtration rate (eGFR), between the ages of 18 and 80 years who had no self-reported history of cardiovascular disease were included. Results: The study participants had a median (interquartile range) of eGFR of 26.62 (15.00 – 38.67) mL/min/1.73m². The data were not normally distributed. The median (IQR) of hs-Troponin T levels was 66 (35.40 – 100.00) ng/L in males and 76.20 (49.00 – 111.00) ng/L in females, with the 99th percentile URL at 402.9 ng/L for males and 264.9 ng/L for females. Therefore, the combined median hs-Troponin T value for both genders was 69.00 ng/L, with an IQR of 40 to 102.75 ng/L. The 99th percentile URL of hs-Troponin T was 394.74 ng/L. A moderate but statistically significant negative correlation, r = -0.4643 (95% CI), between eGFR and hs-Troponin T levels was identified. Conclusion: The 99th percentile URL for hs-Troponin T in CKD patients was markedly elevated compared to that observed in the healthy population. These findings underscore the importance of establishing CKD-specific URL of hs- Troponin T to prevent the misclassification of myocardial infarction..